2018
DOI: 10.1590/abd1806-4841.20183071
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the occurrence of sexual dysfunction and general quality of life in female patients with psoriasis

Abstract: BackgroundPsoriasis has a significant impact on quality of life (QoL). Sexual life can also be affected, with sexual dysfunction being reported by 25-70% of patients.ObjectivesTo determine the occurrence of sexual dysfunction and evaluate QoL in women with psoriasis.MethodsThis case-control study included women aged 18-69 years. The validated Brazilian Portuguese versions of the Female Sexual Function Index (FSFI) and of the Medical Outcomes Study 36-Item Short Form Health Survey (SF-36) were administered to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 41 publications
(44 reference statements)
1
10
0
1
Order By: Relevance
“…In the literature, there are studies reporting the effect of psoriasis on sexual function since 1988 [40]. Many studies have associated psoriasis with a significantly increased prevalence and risk of new-onset dysfunction erectile [40][41][42][43][44][45][46]. Of note, psoriasis can alter patients' body image, resulting in low self-esteem and stigmatization, leading in turn to SD [37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature, there are studies reporting the effect of psoriasis on sexual function since 1988 [40]. Many studies have associated psoriasis with a significantly increased prevalence and risk of new-onset dysfunction erectile [40][41][42][43][44][45][46]. Of note, psoriasis can alter patients' body image, resulting in low self-esteem and stigmatization, leading in turn to SD [37].…”
Section: Discussionmentioning
confidence: 99%
“…Of note, psoriasis can alter patients' body image, resulting in low self-esteem and stigmatization, leading in turn to SD [37]. Similarly, the sexual function seems to be altered in women with psoriasis, although studies are much scarcer in this area [46]. Hidradenitis suppurativa is another inflammatory dermatosis that can be attached to SD.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have followed the sexual dysfunction in patients with psoriasis. These studies over time have found the prevalence of sexual dysfunction in psoriasis ranging from 22.6% to 71.3% 4,36 .…”
Section: Perspectives and Discussionmentioning
confidence: 99%
“…Although it is not thought to affect fertility, pregnancy rates have been observed to be approximately 22% lower in women with psoriasis. Among the reasons for this, it has been suggested that many factors such as women's unwillingness to voluntarily, concerns about pregnancy and/or postpartum disease activity, fear of the effect of psoriasis treatments on pregnancy and baby, as well decreased closeness due to embarrassment and/or physical inability play a role [8,11].…”
Section: Psoriasis and Pre-pregnancy Periodmentioning
confidence: 99%